2015
DOI: 10.3171/2014.12.jns14646
|View full text |Cite
|
Sign up to set email alerts
|

Health disparities and stroke: the influence of insurance status on the prevalence of patient safety indicators and hospital-acquired conditions

Abstract: OBJECT The Agency for Healthcare Research and Quality patient safety indicators (PSIs) and the Centers for Medicare and Medicaid Services hospital-acquired conditions (HACs) are publicly reported quality metrics linked directly to reimbursement. The occurrence of PSIs and HACs is associated with increased mortality and hospital costs after stroke. The relationship between insurance status and PSI and HAC rates in hospitalized patients treated for acute ischemic stroke was determined using the Nationwide Inpati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…[19] The adverse effect of PSI on patient outcomes has been well documented. [21, 32, 33] In addition to the ethical obligation for physicians to provide high quality care for their patients, physician and hospital reimbursement is increasingly tied to care quality. Rajaram et al used CMS, Center for Disease Control (CDC), and Medicare data to show that 721 hospitals (22% of all participating hospitals) were financially penalized for substandard quality of care in the first year (fiscal year 2015) of the CMS HAC Reduction Program.…”
Section: Discussionmentioning
confidence: 99%
“…[19] The adverse effect of PSI on patient outcomes has been well documented. [21, 32, 33] In addition to the ethical obligation for physicians to provide high quality care for their patients, physician and hospital reimbursement is increasingly tied to care quality. Rajaram et al used CMS, Center for Disease Control (CDC), and Medicare data to show that 721 hospitals (22% of all participating hospitals) were financially penalized for substandard quality of care in the first year (fiscal year 2015) of the CMS HAC Reduction Program.…”
Section: Discussionmentioning
confidence: 99%
“…Another study indicated that private insurance is associated with lower mortality, shorter lengths of stay, and improved clinical outcomes [23]. It seems that patients with higher financial capabilities who can be hospitalized in private hospitals have a generally higher safety rate.…”
Section: Discussionmentioning
confidence: 99%
“…Although the incidence of adverse safety events has been quantified in multiple patient populations [3,7,9,14,24,25,35,36], no prior study has quantified the incidence of adverse events in patients undergoing hospitalization for primary spinal cord neoplasms using PSI as a metric. In the present study, we observed a lower incidence of PSI in patients treated for primary spinal cord neoplasms (2.8%) compared to prior studies of other neurosurgical patient populations.…”
Section: Incidence Of Psimentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Although acquiring health insurance may play a role in reducing disparities across socioeconomic groups, [10][11][12] expanding health insurance access does not guarantee that patients receive high quality care. [9,13,14] The Hospital Value Based Purchasing Program, implemented by the Centers for Medicare and Medicaid Services (CMS) as part of the Affordable Care Act (ACA), links healthcare quality with healthcare reimbursements to improve the quality of care received by all patients, regardless of socioeconomic or insurance status. [15,16] CMS measures healthcare quality and patient safety according to a suite of patient safety indicators (PSI) developed by the Agency for Healthcare Research and Quality (AHRQ).…”
Section: Introductionmentioning
confidence: 99%